Human Relations And Working Environment Conditions In Building A Work Ethic With Motivation As Mediation At The Office Of The Agency For Personnel And Human Resources Development (BKPSDM) Sawahlunto City - Nesyia Tri Khairani; Marta Widian Sari; Vivi Nila Sari; Andry Novrianto (UPI YPTK Journal of Business and Economics, 2022)
This study aims to determine the influence of Human Relations and Work Environment Conditions in Building a Work Ethic with Motivation as Mediation at the Office of the Personnel and Human Resources Development Agency (BKPSDM) Sawahlunto City. The method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. By distributing questionnaires as many as 39 respondents. The results of the data analysis concluded that there was a positive and significant influence on the human relation variable on the work ethic variable. There is a positive and insignificant influence on work environment variables on work ethic variables. There is a positive and insignificant influence of the human relation variable on the motivation variable. There is a significant positive effect of the human relation variable on work ethic variables. There is a positive influence which is not significant, the motivation variable has an effect on work ethic variables. There is a positive and insignificant influence given by the human relation variable on the work ethic variable which is mediated by motivation. There is a positive and insignificant influence given by the work environment variable on work ethic variables mediated by motivation.